Does Corporate Social Responsibility Impacts on Employee Engagement? - Ferreira, P. (2014)
Purpose – Despite the claim that internal corporate social responsibility plays an important role, the understanding of this phenomenon has been neglected. This paper intends to contribute to fill this gap by looking into the relation between CSR and employee engagement. Design/methodology/approach – A survey research was conducted and three different groups of respondents were faced with three different CSR scenarios (general, internal, external) and respondents' employee engagement was measured. Findings – The results show that there are no statistically significant differences in levels of engagement between employees exposed to external and internal CSR practices. Nevertheless, employees exposed to internal CSR are more engaged than those exposed only to external CSR practices. Research limitations/implications – The use of scenarios, although a grounded approach, involves risks, including the difficulty of participants to put themselves in a fictional situation. Also, the scale used to measure employee engagement puts the emphasis on work rather than on the organisation. Practical implications – Although this study is not conclusive it raises the need for companies to look at their CSR strategy in a holistic approach, i.e. internal and external. Originality/value – This paper represents a contribution to understand CSR strategic status and the need to enlighten the impact that social responsible practices can have on employees' engagement.